Risk of sound-induced hearing loss from exposure to video gaming or esports: a systematic scoping review - Shelly Chadha; Carolina Der; Xinxing Fu; Lauren K Dillard; Peter Mulas (BMJ Publishing Group, 2024)
Background There is little information on whether video gaming might be a modifiable risk factor for hearing loss and/or tinnitus, despite the plausibility of these relationships given that video games are often played at high-intensity sound levels and for long periods of time.Objective To synthesise current evidence related to relationships between gaming and the potential risk of hearing loss and/or tinnitus.Design Systematic scoping reviewData sources We searched three databases (PubMed, Scopus, Ovid MEDLINE) in January 2023 for peer-reviewed articles, and searched grey literature sources, from inception to 2023.Eligibility criteria Observational, mixed-methods, trials, or case studies published in (or that could be translated into) English, Spanish or Chinese were eligible for inclusion. Studies were included if they evaluated relationships of gaming with hearing loss and/or tinnitus.Data extraction and synthesis Two reviewers extracted and verified study data, which are synthesised in tables and in the text.Results Fourteen peer-reviewed studies were included, 11 of which were cohort studies and 3 of which were non-cohort observational studies. Across studies, the prevalence of gaming ranged from 20% to 78%. In general, the average measured sound levels of video games nearly exceeded, or exceeded, permissible sound exposure limits, and on average, individuals played video games for approximately 3 hours per week. Among the five peer-reviewed studies that evaluated associations or correlations of gaming with hearing loss or tinnitus, four reported significant associations or correlations with gaming and hearing loss or tinnitus.Conclusions The limited available evidence suggests that gaming may be a common source of unsafe listening, which could place many individuals worldwide at risk of permanent hearing loss and/or tinnitus. Additional research on these relationships is needed along with steps to promote safe listening among gamers.